Violence and adolescence in urban settings: A public health approach based on the MLIVEA framework - Susanne Jordan (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
Adolescent violence is a public health issue with global relevance and far-reaching health consequences. It impairs the well-being of those involved and makes demands on health services. The review gives insight into the determinants leading to the health effects of urban violence focusing on young people. For this purpose a new comprehensive framework has been developed and applied. The new framework is called MLIVEA framework due to the structure of its components, which are macro level, local setting, individual level, violent act, health effect and action. Determinants of the macro level are forming societal conditions that contribute to the development of violence in cities. The different local settings are all affected by the macro level and are connecting links to the individual level. The individual level shows risk factors of the individual adolescent concerning psychological, social and biological aspects of personality. The violent acts refer to actual violent events leading to the violence-related health effects. Action can be taken to reduce violence at the macro level, at the local setting level and at the individual level. The advantage of the new framework lies in its presentation of the whole process and the interrelations of factors, which lead to adolescent violence in cities. The MLIVEA framework shows: 1. It is necessary to understand the causes of violence at all the different levels for each city. 2. Best results are gained by carrying out interventions at all the levels. 3. Violence and related health consequences are preventable and have relevance for public health science and action. – – In vielen Ländern gefährden Gewalttaten nicht nur den sozialen Zusammenhalt, sie belasten auch die Gesundheit der Bevölkerung. Insbesondere Jugendliche und junge Erwachsene in Städten sind häufig an Gewalttaten beteiligt, entweder als Opfer oder als Täter. Bei ihnen stellen die gesundheitlichen Folgen von Gewalt eine wichtige Ursache von Mortalität und Morbidität dar. Der Artikel gibt einen Einblick in die Determinanten, die zu den Gesundheitsfolgen von städtischer Gewalt führen und konzentriert sich dabei auf Jugendliche. Für diesen Zweck wurde ein umfassendes Modell entwickelt und angewendet. Das neue Modell wird entsprechend seiner Komponenten MLIVEA genannt: Macro Level, Local Setting, Individual Level, Violent Act, Health Effect und Action. Der Vorteil des Modells liegt in der Darstellung des gesamten Prozesses von der Gewaltentstehung über die Gewalttat und seinen gesundheitlichen Folgen bis hin zu geeigneten Interventionen. MLIVEA zeigt, dass Gewalt und damit zusammenhängende Folgen für die Gesundheit nicht unvermeidbar sind, Präventionsmöglichkeiten durchaus existieren und Public Health dazu beitragen kann, sie zu finden und umzusetzen.
Keywords: 300